Following the Levellers, Volume Two English Political and Religious Radicals from the Commonwealth to the Glorious Revolution, 1649-1688 - De Krey, Gary S. (Palgrave Macmillan UK, 2018)
The Levellers sought to restructure the state in 1647-9 around popular consent and liberty for conscience, especially in their Agreement of the People. Following the Levellers, Volume Two examines the later political efforts of Leveller spokesmen like John Lilburne, John Wildman, and Richard Overton and their followers. Far from ending in the 1649 troop revolts, the Leveller impact continued in the Interregnum climacterics of 1653 and 1659-60, times of acute political and religious unsettlement. Indeed, Leveller ideas resurfaced in Restoration political and religious crises in 1678-83 and again in 1687-8 and flourished in populations that once followed the Levellers. Analysis of London, army, and county Levellers reveals connections to subsequent outbursts of unrest. Sectarian communities in London's peripheral neighbourhoods and nearby counties sustained the Leveller ethos, and ordinary people like those who followed the Levellers remained active in petitioning and protest about political and religious liberties through the Glorious Revolution.